Propuesta de aplicación de arquitectura de empresarial para una empresa pública metropolitana de Quito, con el propósito de reducir el impacto sobre proyectos tecnológicos de la institución ante un cambio de autoridades - Castillo Escobar, Edgar Alexander (2016)
The activities entrusted to the Metropolitan Public Company of Quito impact directly in the benefit of the people living in the capital of Ecuador, which is why these activities have to be analyzed for their implementation and should maintain continuity despite any change of new authorities within the company. On several occasions Information technology projects that support the various managements or organizational units within the company, are categorized with low priority and often without any priority, due to the lack of knowledge of the new incoming authorities about these projects, that without a doubt they certainly automate and streamline tasks running in the company. It is very common that the new authorities bring with them their trusted team, which take some time to be aware of the projects the company is running, and delays decision making which causes activities not to flow adequately and take unexpected turns, causing the use of resources not optimally utilized which have a negative impact to Information technology projects of different areas within the organization, thus affecting the stability of the services that the company offers to the public. The role of the professionals in Information Technology is not only provide services as it is today, but should focus on generate projects that add value to the business processes and in this particular case as being a Metropolitan Public Company, these projects reflect directly the management that the authorities make to improve the wellbeing of capital of Ecuador.